Nanoscale hydrodynamics of simple systems - Hansen, Jesper Schmidt 1973- (Cambridge University Press, 2022)
Written for graduate students and researchers, Nanoscale Hydrodynamics of Simple Systems covers fundamental aspects of nanoscale hydrodynamics and extends this basis to examples. Covering classical, generalised and extended hydrodynamic theories, the title also discusses their limitations. It introduces the reader to nanoscale fluid phenomena and explores how fluid dynamics on this extreme length scale can be understood using hydrodynamic theory and detailed atomistic simulations. It also comes with additional resources including a series of explanatory videos on the installation of the code package, as well as discussion, analysis and visualisations of simulations. This title primarily focusses on training the reader to identify when classical theory breaks down, how to extend and generalise the theory, as well as assimilate how simulations and theory together can be used to gain fundamental knowledge about the fluid dynamics of small-scale systems.